Contesting Commemorative Landscapes: Confederate Monuments and Trajectories of Change. (30th December 2020) - Simko, Christina; Cunningham, David; Fox, Nicole
Abstract: Following the racially motivated shootings at an African American church in Charleston, South Carolina, in 2015, a wave of contentious campaigns around Confederate statuary emerged, or at least intensified, in communities across the country. Yet local struggles have culminated in vastly different alterations to the built environment. This paper develops a framework for differentiating distinct "modes of recontextualization" rooted in the relocation and/or modification of commemorative objects. Building on models of memory as an iterative, path-dependent process, we track recontextualization efforts in three communities—St. Louis, Missouri; Oxford, Mississippi; and Austin, Texas—documenting how each mode alters the meaning of contested symbols. An analysis of local news sources in the year following recontextualization shows how each mode exerts identifiable proximate effects on broader political debates and, through that process, structures the horizon of possibility for longer-range outcomes.